Why can't we predict earthquake? - Radice, Mark (Frenchs Forest, N.S.W. : BBC Active, 2009)
Capable of ripping up roads, moving mountains and tearing down towns, they're the biggest force of natural destruction on the planet. They affects parts of every continent. Billions of dollars, yen and yuan are being poured into researching these hazards. A major earthquake striking Los Angeles would cause over $200 billion in property damage. And yet, remarkably, when earthquakes hit, they invariably take us by surprise. This film asks the question that is bugging geologists, seismologists, town planners, big businesses and ordinary people alike, in seismic zones all over the globe; how can we predict an earthquake?
Originally broadcast as a segment of the television program: Horizon.
Series producer, James van der Pool ; photography, Mike Robinson ; editor, Andrew Cohen.
Narrated by: Steven Mackintosh.
dvd format
Keywords: Earthquakes; Earthquake prediction